The sectoral effects of value-added tax: Evidence from UAE stock markets - Anagha Ann Gopakumar; Avneet Kaur; Vikash Ramiah; Krishna Reddy (Journal of Risk and Financial Management, 2022)
This paper investigates the impact of 19 announcements pertaining to the introduction of value-added tax (VAT) in the United Arab Emirates (UAE) on equities listed on the Abu Dhabi Stock Exchange (ADX). Using a well-established event study methodology over the period 2015 to 2018, a sector-wise assessment of the value constructiveness or destructiveness of these announcements is conducted. In addition, an estimation of sector-wise changes in systematic risk following these announcements is provided. Significant sectoral differences in abnormal returns are observed with industries such as insurance and retail showing higher sensitivity. Certain announcements are identified as exerting more impact than others. The results document the outcome of the implementation of VAT and provide guidance to other countries in the Gulf region that plan to introduce VAT.
Keywords: G12; G14; H25; 650; value-added tax; abnormal returns; systematic risk